Recurrent Extradural Myxopapillary Ependymoma With Oligometastatic Spread - Batich, Kristen A.; Riedel, Richard F.; Kirkpatrick, John P.; Tong, Betty C.; Eward, William C.; Tan, Char Loo; Pittman, Patricia D.; McLendon, Roger E.; Peters, Katherine B. (Frontiers in Oncology, 2019)
Myxopapillary ependymomas are a slow-growing, grade I type glial tumor in the lumbosacral region. More rarely, they can present as extradural, subcutaneous sacrococcygeal, or perisacral masses, and it is under these circumstances that they are more likely to spread. Here, we report the presentation of a sacrococcygeal mass in patient that was initially resected confirming extradural myxopapillary ependymoma. At initial resection, multiple small pulmonary nodules were detected. This mass recurred 2 years later at the resection site with an interval increase in the previously imaged pulmonary nodules. Resection of both the post-sacral mass and largest lung metastasis confirmed recurrent myxopapillary ependymoma with oligometastatic spread. Because these tumors are rare, with extradural presentation being even more infrequent, to this date there are no definitive therapeutic guidelines for initial treatment and continued surveillance. For myxopapillary ependymoma, current standard of care is first-line maximal surgical resection with or without postoperative radiotherapy depending on the extent of disease and extent of resection. However, there remains insufficient evidence on the role of radiotherapy to oligometastatic foci in providing any further survival benefit or extending time to recurrence. Thus, prospective studies assessing the role of upfront treatment of oligometastases with local resection and adjuvant radiotherapy are needed for improved understanding of extradural myxopapillary ependymoma.